Does Competitive Advantage Mediate the Relationship between Innovation and Business Performance? - Muis, Indra (International Journal of Advanced Multidisciplinary, 2025)
The aim of the study is to describe product innovation implementation and marketing innovation implementation, competitive advantage of private Vocational Higher Education Institutions (VHEIs), and their business performances. The study is also to examine the effects of product innovation and marketing innovation on business performance which is mediated by competitive advantage. The unit analysis is leaders of private VHEIs operating in West Java Province Indonesia. This research applies quantitative methods. The populations of the research were 118 private VHEIs in West Java Province, Indonesia and the respondents were 100 leaders of private VHEIs.The sampling technique is simple random sampling. And the study uses the Partial Least Square technique for data analysis. The findings are both product innovation and marketing innovation have positive effects on competitive advantage. Besides, they also have positive effects on business performance. Furthermore, competitive advantage mediates the innovation – business performance relationship. The leaders of VHEIs need to implement product and marketing innovation as well as their competitive advantage to improve their business performance.